(untitled) (Fiep Bulletin - online, 2011)
This present work is the evolution from the Article published on the FIEP’s International Scientifc Journal, vol. 77 – FIEP BOLETIN Special Edition II, 1 PAG 162. The goal at that moment was to identify ways that the Physical Education Teacher can take to improve the motor repertory of students diadnosed with autism. Now, this present contribution works on the evolution of this article mentioned and is based on the criterions of organization of the subjects: continuity, sequence and integration, aiming to help professionals that work with education and health, as well as the student’s family. This search procedure becomes relevant due to the importance of the subject and the absence of literature available in Brazil. The classes that we based this application started in 2006, instructing a hundred of children at regular schools, hotels and clubs, continuing until nowadays. This work is based on the methodologie psicomotricity. The project was almost totaly developed and applied by the teacher Daniel L. Candido and ways oriented by Ms. Sérgio Eduardo Santos de Moura. The results reached are directaly relationed with the geral improvement of language, enlarging comprehension and expression of students observed with a bigger motor repertory, academic and communicative, as well as the evolution of physical qualities, possibiliting psicomotor maturity and several students’ adaptations to their daily activities, satisfaction and expressive socialization.